Enhancing Delivery and Assessment: A Case Study in Module Redesign for Improved Transition Into Higher Education. Issue 3 (3rd July 2018) - Barr, Matthew; Jackson, Louise H.
ABSTRACT: Understanding student transition into higher education is an important aspect of module design, linking content, delivery, and assessment with a student's prior educational experience and knowledge bases. However, reflections on how modules designed choices are, generally, not widely disseminated. Here, we document the reflections of a junior lecturer responsible for redesigning a Level-4 Political Systems module and analyze the intentions of change via a transition pedagogy perspective, presenting a program renewal that establishes connected curriculum as an enabling infrastructure for students to actively engage with learning. First-year experience is considered as a major impacting factor of a student's subsequent success on a program of higher education and the diversification of student cohorts requires teaching staff to consider a wider number of intersectional factors that may impact on a student's opportunity to succeed in their studies. With a focus on simulations and active-learning, by providing examples of the thinking behind the resultant activities and assessment realignment we hope to provide an example of how a transition approach to a first-year module can be explored.